Preparation method and application of monatomic nano-enzyme

Metal single-atom nanoenzyme prepared by graphite phase carbon nitride support and grinding and calcining method solves the problem of insufficient stability and catalytic activity of single-atom nanoenzymes, achieves efficient catalysis and stability, and has a wide potential for biomedical application .

CN119456009APending Publication Date: 2025-02-18XIAMEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411596140.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing single-atom nanoenzymes have poor stability in isolated atoms during the synthesis process, which is prone to agglomeration, affecting catalytic activity, and insufficient support selection.

Method used

The metal single-atom nanoenzyme was prepared by grinding, mixing and calcining using graphite phase carbon nitride as a support, and metal active sites were exposed using the pores of g-C3N4 and the high specific surface area to improve atomic utilization and stability.

Benefits of technology

It significantly improves the catalytic activity and stability of single-atom nanoenzymes, reduces synthesis costs, enhances the killing ability of tumor cells, and has a wide range of antibacterial and anti-tumor application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119456009A_ABST
    Figure CN119456009A_ABST
Patent Text Reader

Abstract

The invention relates to the field of nano biomedical materials, aims to provide a preparation method and application of monatomic nano-enzyme, and particularly relates to a preparation method of graphite-phase carbon nitride loaded metal monatomic nano-enzyme and application of the graphite-phase carbon nitride loaded metal monatomic nano-enzyme in tumor resistance. The preparation method comprises the following steps: S1, preparing a g-C3N4 substrate: taking dicyandiamide and potassium iodide, and performing ball milling, calcination and grinding to obtain the g-C3N4 substrate; s2, preparing monatomic nano-enzyme: grinding and mixing a metal compound and a g-C3N4 substrate, and drying and calcining to obtain a crude product; and performing ultrasonic crushing, washing and drying on the crude product to obtain the monatomic nano-enzyme. According to the monatomic nano-enzyme provided by the invention, metal active sites can be exposed to the greatest extent, the Fenton or Fenton-like catalytic activity is improved, and the synthesis cost of the monatomic nano-enzyme is reduced; the g-C3N4 nitrogen carbon compound is adopted as a carrier, the stability of isolated atoms is improved, and the agglomeration phenomenon is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nano-biomedical materials, and relates to a preparation method and application of a single-atom nanozyme, and specifically to a preparation method and application of a graphite-phase carbon nitride-loaded metal single-atom nanozyme. Background Art

[0002] Cancer has the characteristics of high incidence and high mortality rate, which poses a huge threat to people's health. Cancer treatment has always been an important research direction in the medical field. Existing cancer treatment programs have obvious side effects, bone marrow transplant matching is difficult, and chemotherapy and radiotherapy kill cancer cells while also causing great damage to normal cells. Therefore, people have been committed to developing new cancer treatment programs.

[0003] Natural enzymes are an indispensable and efficient catalyst in organisms, which maintain the normal life activities of organisms. Nanozymes, as a material with high stability and low cost that simulates the activity of natural enzymes, largely make up for the shortcomings of harsh reaction conditions, poor stability and high cost of natural enzymes, and have been widely used in various fields such as biosensing, disease treatment, and environmental governance instead of natural enzymes. However, the metal atom utilization rate of nanozymes is low and the active sites are unstable. Currently, efforts are being made to construct nanozyme materials with efficient catalytic activity. Single-atom nanozymes have attracted widespread attention for their extremely high atomic utilization rate and excellent enzyme-like activity. They have been widely used in various fields such as antibacterial, anti-tumor, and biosensing.

[0004] Copper death and ferroptosis provide new ideas for disease treatment. Ferroptosis is a non-apoptotic cell death mode caused by the accumulation of iron-dependent lipid peroxides (LPO). Glutathione peroxidase 4 (GPx-4) can effectively regulate ferroptosis, which uses glutathione (GSH) as a cofactor to reduce LPO. The consumption of GSH can inactivate GPx-4 and induce the irreversible production of LPO, but glutathione oxidase (GSHOx) promotes the conversion of GSH to glutathione disulfide bonds (GSSG), leading to the inactivation of GPx-4, thereby increasing the accumulation of LPO. Fe single-atom nanozymes have been found to have GSHOx-like activity, which can effectively induce the death of tumor cells and are therefore widely used in cancer treatment. Copper death mainly occurs in mitochondria, Cu 2+ By directly binding to the lipid components of the tricarboxylic acid cycle (TCA) pathway, it affects the regulatory process of the ferredoxin (FDX1) gene, causing abnormal aggregation of lipoyl proteins and loss of Fe-S cluster proteins in the respiratory chain complex, ultimately leading to an acute protein toxicity stress response and directly inducing cell death. It has great application potential in anti-tumor.

[0005] The main difficulty in synthesizing single-atom nanozymes is the stability of the isolated atoms. Aggregation is very easy to occur during the synthesis of single-atom nanozymes, and this aggregation trend will seriously affect the catalytic activity of the material. The carrier determines the dispersion, uniformity and stability of the single atom, so the carrier selection for the synthesis of single-atom nanozymes is very important. Nitrogen-carbon compounds can perform catalysis and photocatalysis by themselves. Their interconnected pores and high specific surface area can expose the active sites of isolated atoms to the greatest extent. And because of the high content of coordination sites provided by nitrogen atoms, they have chemical and thermal stability and become superior carriers for single atoms. Carbon-nitrogen compounds are a reliable carrier for the synthesis of single-atom nanozymes. Reasonable design of the structure of porous graphite phase carbon nitride (Pg-C3N4) can maximize the utilization of atoms and greatly improve the performance of single-atom materials.

[0006] CN112973750B relates to a carbon quantum dot-coated metal single atom-carbon nitride composite material and a preparation method thereof, wherein the material uses graphite phase carbon nitride as a carrier, loads metal single atoms coated with carbon quantum dots, and realizes the preparation of carbon quantum dot-coated metal single atom / carbon nitride composite material by coordination and constant temperature roasting method, and prevents metal single atom agglomeration by using carbon quantum dots to coat metal single atoms, but does not provide relevant technical inspiration for improving the stability of isolated atoms. CN112844431A discloses a preparation method of a copper ion chelated graphite phase monolayer C3N4 nanozyme, which uses melamine and CuCl2 as precursors, and constructs a copper ion chelated graphite phase monolayer C3N4 nanozyme material by calcination and ultrasound, and the nanozyme is copper ion chelated, and has deficiencies in catalytic activity.

[0007] Based on this, it is necessary to provide a preparation method and application of single-atom nanozymes to improve their catalytic activity and the stability of isolated atoms. Summary of the invention

[0008] The purpose of the present invention is to provide a preparation method and application of a single-atom nanozyme, and specifically to a preparation method of a graphite phase carbon nitride-loaded metal single-atom nanozyme and its application in anti-tumor. The single-atom nanozyme provided by the present invention can expose the metal active site to the greatest extent, improve the Fenton or Fenton-like catalytic activity, and reduce the synthesis cost of the single-atom nanozyme; the structure of the single-atom nanozyme of the present invention is similar to the geometric structure of the natural enzyme, and has excellent enzyme-like activity; g-C3N4 nitrogen-carbon compound is used as a carrier to improve the stability of isolated atoms and reduce agglomeration. And the preparation method of the present invention can adjust the loading amount of metal single atoms in g-C3N4 by changing the amount of metal compound added, so as to obtain a single-atom nanozyme with a higher metal loading amount.

[0009] To achieve the above object, the technical solution of the present invention is as follows:

[0010] On the one hand, the present invention provides a method for preparing a graphite phase carbon nitride-supported metal single-atom nanozyme, comprising the following steps:

[0011] S1: preparing g-C3N4 substrate: taking dicyandiamide and potassium iodide, and preparing g-C3N4 substrate by ball milling, calcining and grinding;

[0012] S2: Preparation of single-atom nanozymes: Grind and mix the metal compound and the g-C3N4 substrate, and obtain a crude product through drying and calcination; the crude product is ultrasonically crushed, washed, and dried to obtain a single-atom nanozyme.

[0013] Furthermore, the mass ratio of dicyandiamide to potassium iodide is 1:1-5, preferably 1:2, 1:3, 1:4, etc.

[0014] Further, in S1, the calcination refers to placing the ball-milled mixture in a tube furnace under the protection of an inert gas, heating the mixture from 20 to 30 ° C to 300 to 650 ° C at a rate of 1 to 5 ° C / min and keeping it warm for 1 to 6 hours, and naturally cooling it down to room temperature. Further, in S1, the calcination refers to placing the ball-milled mixture in a tube furnace under the protection of an inert gas, heating the mixture from 30 ° C to 550 ° C at a rate of 5 ° C / min and keeping it warm for 6 hours, and naturally cooling it down to room temperature. Further, in S1, the calcination is carried out in a tube furnace. Further, the inert gas refers to argon (pure Ar gas), and the gas flow rate is 5 to 30 mL / min.

[0015] Furthermore, in S1, the grinding is performed in an agate mortar.

[0016] Furthermore, in S2, the metal compound is a copper salt, preferably solid CuCl2·2H2O.

[0017] Furthermore, in the single-atom nanozyme, the Cu element content loaded on every 2 g of g-C3N4 substrate is 0.05 mmol to 1.5 mmol, preferably 0.1 mmol to 0.15 mmol.

[0018] Further, in S2, the grinding and mixing is carried out in anhydrous ethanol. Further, in S2, the grinding and mixing refers to grinding the metal compound and carbon nitride in anhydrous ethanol until the anhydrous ethanol volatilizes, wherein the role of anhydrous ethanol is to protect the metal compound and avoid oxidation during the grinding process, which affects the subsequent experimental results; and to enable the metal compound powder and the carbon nitride powder to be mixed evenly for easy grinding. Preferably, in S2, the volume ratio of anhydrous ethanol used in the grinding and mixing step to the mass ratio of the g-C3N4 substrate is 1mL / g.

[0019] Furthermore, in S2, the drying refers to drying in an oven at 50-70°C overnight, preferably, the drying refers to drying in an oven at 60°C overnight.

[0020] Further, in S2, the calcination refers to calcination in an inert gas. Further, the inert gas refers to argon (pure Ar gas). Further, the flow rate of the inert gas is 25 to 35 mL / min. Preferably, it is 30 mL / min.

[0021] Further, in S2, the calcination refers to heating from 20 to 30°C to 400 to 450°C at a rate of 1 to 5°C / min in an inert gas and keeping the temperature for 1 to 4 hours, and naturally cooling down to room temperature. Further, in S2, the calcination refers to heating from 30°C to 450°C or 400°C at a rate of 5°C / min in an inert gas and keeping the temperature for 2 hours, and naturally cooling down to room temperature.

[0022] Further, in S2, the ultrasonic crushing process is: the crude product is dispersed in pure water, ultrasonically crushed at a constant temperature and 100W for 1 to 8 hours, preferably for 6 hours, and the supernatant is removed by centrifugation. The ultrasonic crushing and centrifugation process are repeated twice, and the obtained precipitate is further ultrasonically crushed and centrifuged to obtain a precipitate. Further, the centrifugal speed of the centrifugation is 5000 to 6500rpm, and the centrifugation time is 10 to 15min. Further, in S2, the ultrasonic crushing is repeated twice to remove residual potassium iodide impurities. Further, the ultrasonic crushing process in S2 is: ultrasonically crush the precipitate for 1 to 20 minutes, preferably 10 to 15 minutes, centrifuge, the centrifugal speed is 11000rpm, and the centrifugation time is 1 to 10 minutes; take the precipitate and add 30mL of pure water to ultrasonicate again for 1 to 5 minutes, centrifuge at 11000rpm for 1 to 10 minutes to obtain a precipitate. The purpose of this operation is to obtain single-atom nanozyme particles with smaller particle size and better dispersion.

[0023] On the other hand, the present invention provides a graphite-phase carbon nitride-loaded metal single-atom nanozyme, which uses graphite-phase carbon nitride as a carrier, and the Cu element content loaded per 2g of g-C3N4 substrate is 0.05mmol~1.5mmol, preferably, 0.1mmol~0.15mmol.

[0024] Furthermore, the single-atom nanozyme is prepared using the method described in the present invention.

[0025] On the other hand, the present invention provides an application of graphene-phase carbon nitride-loaded metal single-atom nanozyme in anti-tumor aspects.

[0026] Compared with the prior art, the beneficial technical effects of the present invention are as follows:

[0027] 1. Compared with the widely used nanozymes today, the single-atom nanozymes of the present invention can make the most of the active sites of metal atoms, and use the method of directly loading metal atoms on graphite phase carbon nitride to improve the Fenton / Fenton-like catalytic activity and enzyme-like activity of single-atom nanozymes. The main factor affecting the catalytic performance of nanozymes is the size of metal particles. A series of theoretical and experimental results show that sub-nanoclusters have better catalytic activity and selectivity than nanoscale particles. Therefore, it is very desirable to reduce particles or clusters to single atoms for catalytic reactions. From a microstructural perspective, as the size of metal materials decreases, the number of atoms on the surface of the material increases, and the catalytic activity is also improved. Characterized by particle size, such as Figures 1 to 3 The particle size of the Cu single-atom nanozyme of the present invention is less than 100 nm, which can effectively improve the catalytic activity.

[0028] 2. The present invention uses graphite phase carbon nitride as a substrate. Since the pores and high specific surface area connected by carbon nitride can expose the active sites of isolated atoms to the greatest extent, and the coordination sites provided by nitrogen atoms in carbon nitride have a high content, chemical and thermal stability, and are superior carriers for preparing single-atom nanozymes, greatly improving the stability of single-atom nanozymes during use. The present invention uses graphite phase carbon nitride as a substrate and optimizes it. Since the pores and high specific surface area connected by carbon nitride can expose the active sites of isolated atoms to the greatest extent, and since the coordination sites provided by nitrogen atoms therein have a high content, chemical and thermal stability, it is an excellent carrier for preparing single-atom nanozymes, greatly improving the stability of single-atom nanozymes during use. The carbon nitride synthesized in the present invention is different from conventional g-C3N4-based nanomaterials. In the absence of any surface modification, the single-atom nanozyme with it as a carrier can maintain good stability under different environments. In the present invention, the Cu single-atom nanozyme does not show obvious precipitation after long-term standing. After observation, no obvious precipitation was observed after at least 3 days of standing, indicating that the single-atom nanozyme has good stability and dispersibility. When the nanoparticles prepared by the method of the present invention are placed in a simulated blood circulation environment and left to stand for 7 days, no obvious nanoparticle aggregation phenomenon occurs, indicating that the nanoparticles have good stability and can exist stably in the blood circulation system.

[0029] 3. The single-atom nanozyme of the present invention is simple to operate. It uses grinding, mixing and calcination methods to prepare stable single-atom nanozymes, which improves the repeatability of the experiment, reduces the cost of preparation, and solves the disadvantage of high cost of extracting natural enzymes.

[0030] 4. Peroxidase can catalyze H2O2 to produce ROS(·OH). The occurrence of such catalytic process can produce cytotoxic ROS(·OH), which usually destroys the integrity of cell membranes and is extremely toxic to bacterial cells, achieving efficient sterilization.

[0031] like Figures 4 to 6 As shown, the single-atom nanozyme of the present invention has excellent peroxidase-like activity, so it has great application potential in antibacterial applications. At the same time, the present invention has been proven to have the ability to produce a variety of reactive oxygen species, and when the ROS level exceeds the normal level, it will induce oxidative stress, leading to tissue dysfunction or cell death. This property can be used for anti-tumor treatment.

[0032] The single-atom nanozyme system prepared by the method of the present invention was used for in vitro cell experiments and in vivo anti-tumor evaluation. It was found that this type of single-atom nanozyme has good biosafety for normal cells. 4T1 tumor cells can effectively absorb the nanozyme to produce a large amount of toxic ROS in tumor cells, which has obvious killing ability to cells. In vivo anti-tumor evaluation proved that the single-atom nanozyme can passively target and enrich in the tumor site, inhibiting its growth. At the same time, the physiological indicators of mice are normal and the main organs are not damaged.

[0033] The single-atom nanozyme of the present invention has good dispersibility, can produce a variety of reactive oxygen species, and can be used for tumor treatment; and has a variety of excellent enzyme-like activities, and has broad application potential in multiple biomedical fields such as antibacterial and anti-tumor.

[0034] Terminology

[0035] Certain embodiments of the present invention are now described in detail. The present invention is intended to cover all substitutions, modifications and equivalent technical solutions, which are all included in the scope of the present invention as defined in the claims. It should be appreciated by those skilled in the art that many methods and materials similar or equivalent to those described herein can be used to practice the present invention. The present invention is by no means limited to the methods and materials described herein. In the event that one or more of the combined documents, patents and similar materials are different from or contradictory to the present application (including but not limited to defined terms, term applications, described technologies, etc.), the present application shall prevail.

[0036] It should be further appreciated that certain features of the invention, which for clarity are described in multiple separate embodiments, may also be provided in combination in a single embodiment. Conversely, various features of the invention, which for brevity are described in a single embodiment, may also be provided separately or in any suitable sub-combination.

[0037] Unless otherwise specified, all technical terms used in the present invention have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. All patents and publications related to the present invention are incorporated herein by reference in their entirety.

[0038] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0039] In the following, all numbers disclosed herein are approximate, regardless of whether the words "about" or "approximately" are used. The value of each number may vary by 1%, 2%, 5%, 7%, 8%, 10%, 15% or 20%. Whenever a number having a value of N is disclosed, any number having a value of N+ / -1%, N+ / -2%, N+ / -3%, N+ / -5%, N+ / -7%, N+ / -8%, N+ / -10%, N+ / -15% or N+ / -20% is explicitly disclosed, where "+ / -" means plus or minus. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a transmission electron micrograph of the g-C3N4 / Cu single-atom nanozyme obtained in Example 1 of the present invention. As shown in the figure, the structure of the single-atom nanozyme prepared by the present invention is similar to the geometric structure of the natural enzyme, and there is almost no agglomeration phenomenon. Figure 1 (a) (b) are transmission images of 0.1 mmol Cu-C3N4, (c) (d) are transmission images of 0.15 mmol Cu-C3N4.

[0041] Figure 2 This is the XRD diagram of the g-C3N4 / Cu single-atom nanozyme obtained in Example 1 of the present invention. From the XRD spectrum, it is found that the sample does not contain copper oxide, and there is no diffraction peak of Cu element, indicating that Cu is uniformly dispersed in the g-C3N4 matrix in the form of single atoms.

[0042] Figure 3 This is the particle size distribution diagram of the g-C3N4 / Cu single-atom nanozyme obtained in Example 1 of the present invention. The sample is a small-sized copper single-atom nanoparticle (particle size less than 100nm), which meets the standards for application to organisms.

[0043] Figure 4This is the MB degradation experimental absorption curve of the g-C3N4 / Cu single-atom nanozyme with four Cu loading amounts obtained in Example 1 of the present invention. The sample has good MB degradation ability, proving that the sample can produce a considerable number of hydroxyl radicals.

[0044] Figure 5 The singlet oxygen generation experimental absorption curves of the g-C3N4 / Cu single-atom nanozymes with four Cu loading amounts obtained in Example 1 of the present invention prove that the samples have good singlet oxygen generation capabilities.

[0045] Figure 6 The absorption curves of the TMB degradation experiment of the g-C3N4 / Cu single-atom nanozymes with four Cu loading amounts obtained in Example 1 of the present invention show that the four samples with different Cu loading amounts all showed obvious absorption peaks at 652 nm, and the samples had good peroxidase-like activity. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.

[0047] The reagents used in the present invention can be purchased from the market or prepared by the method described in the present invention.

[0048] The technical solution of the present invention is illustrated below by way of example, and the scope of protection requested by the present invention includes but is not limited to the following embodiments.

[0049] Example 1 Preparation of graphite carbon nitride supported Cu single atom nanozyme

[0050] Weigh 2 g of dicyandiamide and 6 g of potassium iodide, mix them evenly by ball milling, put them into a tubular furnace under the protection of pure argon (Ar) (gas flow rate 30 mL / min), heat them from 30 °C to 550 °C at a rate of 5 °C / min and keep them warm for 6 h, cool them naturally to room temperature, and finally grind the calcined material in an agate mortar to obtain a yellow powdery C3N4 substrate.

[0051] Weigh different amounts of copper chloride dihydrate (CuCl2·2H2O) and 2g of C3N4 substrate and grind them in 2mL of anhydrous ethanol until the anhydrous ethanol evaporates completely to prepare C3N4-Cu with different molar ratios. The ground samples were placed in a 60°C oven for drying overnight, placed in a tube furnace under the protection of pure argon, heated from 30°C to 450°C at a rate of 5°C / h and kept warm for 2h, and naturally cooled to room temperature to obtain C3N4-Cu powder samples with different Cu loadings, as shown in Table 1.

[0052] Table 1

[0053] Cupric chloride dihydrate dosage <![CDATA[Molar amount of Cu loading in the C3N4-Cu powder sample]]> Example 1-1 0.025g 0.15mmol Example 1-2 0.017g 0.1mmol Examples 1-3 0.0128g 0.075mmol Examples 1-4 0.0085g 0.05mmol

[0054] The obtained C3N4-Cu powder was dispersed in 80mL pure water and ultrasonically crushed in a water bath at 25°C for 6h. Centrifuge at 6500rpm for 10min to remove the supernatant, and repeat twice. Ultrasonic crush the obtained precipitate for 10min and centrifuge at 11000rpm for 10min to collect the supernatant. Take the precipitate obtained by the above operation, add 30mL pure water, ultrasonicate again for 5min, and centrifuge again at 11000rpm for 10min to collect the supernatant. The precipitate was washed with pure water several times, dried and collected to obtain four C3N4-Cu suspensions and powder samples with different Cu loadings. In order to obtain a sample with higher purity, 3mL of the C3N4-Cu suspension obtained in the above steps was taken for ultracentrifugation (21000rpm, 10min) and the supernatant was collected. After washing the precipitate twice with pure water at the same speed, it was dispersed in 1mL pure water and collected for storage.

[0055] Example 2 Performance study of graphite carbon nitride-supported Cu single-atom nanozyme

[0056] The four different samples of Example 1 were subjected to MB degradation experiment, singlet oxygen generation detection, TMB color development experiment and NOX-like activity detection.

[0057] 1. MB degradation experiment: prepare 30mg / L MB solution, 20mM H2O2, and samples of known concentrations of 0.15% C3N4-Cu, 0.1% C3N4-Cu, 0.075% C3N4-Cu, and 0.05% C3N4-Cu. Add MB, pure water, sample, and H2O2 in this order to prepare a 5mL system. The final concentration of MB is 6mg / L, and the final concentrations of H2O2 are 10, 5, and 10 mg / L, respectively.

[0058] 1, 0mM, the final concentration of the sample is 100μg / mL. Observe the fading, use an ELISA reader to detect the absorbance curve of the sample at 30min and 60min, and pay attention to the change in absorbance at 654nm.

[0059] 2. Singlet oxygen generation detection: prepare phosphate buffer (PBS, pH 6.5), 100mM H2O2, 6mM DPBF, 0.85mg / mL 0.15% C3N4-Cu, 0.1% C3N4-Cu, 0.075% C3N4-Cu samples and 0.35mg / mL 0.05% C3N4-Cu sample solution. Set up experimental group and control group. The experimental group adds PBS, sample, DPBF, and H2O2 in the order of adding materials, and configure 1mL system so that the final concentration of DPBF is 100μM, 200μM, and 500μM, respectively, the final concentration of sample is 100μg / mL, and the final concentration of H2O2 is 10mM. The control group is divided into a group containing H2O2 and a group without H2O2. Shake well, observe the fading of the sample, and use an enzyme-labeled instrument to detect the absorbance curve of the sample at 0 min, 10 min, 20 min and 30 min, paying attention to the absorbance change at 410 nm.

[0060] 3. TMB color development experiment: prepare phosphate buffer (PBS, pH 6.5), 10mM H2O2, 10mM TMB, and samples for singlet oxygen generation detection. This experiment is divided into tests with H2O2 and tests without H2O2, and experimental and control groups are set up respectively. Add samples in the order of PBS, sample, TMB, and H2O2, and configure them into 1mL system. The final concentration of TMB is 500μM, and the final concentration of the sample is 100μg / mL. Shake well, observe the color development of the sample, use an enzyme marker to detect the absorbance curve of the sample after color development, and pay attention to the absorbance change at 652nm.

[0061] 4. Detection of NOX-like activity: Thaw reagents IV, V, and VI in the NADH oxidase kit in a 37°C water bath, and take 0.15% C3N4-Cu, 0.1% C3N4-Cu, 0.075% C3N4-Cu, and 0.05% C3N4-Cu samples for the experiment. Add 40μL sample, 700μL reagent IV, 100μL reagent V, and 160μL reagent VI to the centrifuge tube. After shaking, observe the fading of the sample, and use an ELISA reader to detect the absorbance curves of the 0min and 30min samples, paying attention to the absorbance changes at 600nm.

[0062] It was found that the single-atom nanozyme prepared in this application has the ability to generate OH and 1 O2 and other active oxygen, which is positively correlated with the Cu loading in the material; and has good enzyme-like activity, which can be used in biomedical treatment. The specific results are as follows Figures 4 to 6 shown.

[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a graphite phase carbon nitride-supported metal single-atom nanozyme, characterized in that: The following steps are involved: S1: preparing g-C3N4 substrate: taking dicyandiamide and potassium iodide, and preparing g-C3N4 substrate by ball milling, calcining and grinding; S2: Preparation of single-atom nanozymes: Grind and mix the metal compound and the g-C3N4 substrate, and obtain a crude product through drying and calcination; the crude product is ultrasonically crushed, washed, and dried to obtain a single-atom nanozyme.

2. The preparation method according to claim 1, characterized in that: The mass ratio of dicyandiamide to potassium iodide is 1:1-5, preferably 1:2, 1:3 or 1:

4.

3. The preparation method according to claim 1, characterized in that: In S1, the calcination refers to placing the ball-milled mixture in a tubular furnace under the protection of an inert gas, heating it from 20 to 30°C to 300 to 650°C at a rate of 1 to 5°C / min and keeping it warm for 1 to 6 hours, and then naturally cooling it down to room temperature; the calcination is carried out in an inert gas, and the inert gas refers to argon, and the gas flow rate is 5 to 30 mL / min.

4. The preparation method according to claim 1, characterized in that: In S2, the metal compound is a copper salt, preferably solid CuCl2·2H2O; Furthermore, in the single-atom nanozyme, the Cu element content loaded on every 2 g of g-C3N4 substrate is 0.05 mmol to 1.5 mmol, preferably 0.1 mmol to 0.15 mmol.

5. The preparation method according to claim 1, characterized in that: In S2, the grinding and mixing is carried out in anhydrous ethanol; the volume ratio of anhydrous ethanol to the mass ratio of the g-C3N4 substrate in the grinding and mixing step is 1 mL / g; Furthermore, in S2, the drying refers to drying in an oven at 50-70°C overnight, preferably, the drying refers to drying in an oven at 60°C overnight.

6. The preparation method according to claim 1, characterized in that: In S2, the calcination refers to calcination in an inert gas; the inert gas refers to argon; the flow rate of the inert gas is 25 to 35 mL / min, preferably 30 mL / min; Further, in S2, the calcination refers to heating the temperature from 20-30°C to 400-450°C at a rate of 1-5°C / min in an inert gas and keeping it warm for 1-4 hours, and naturally cooling it down to room temperature; further, in S2, the calcination refers to heating the temperature from 30°C to 450°C or 400°C at a rate of 5°C / min in an inert gas and keeping it warm for 2 hours, and naturally cooling it down to room temperature.

7. The preparation method according to claim 1, characterized in that: In S2, the ultrasonic crushing process is as follows: the crude product is dispersed in pure water, and ultrasonically crushed at a constant temperature and 100W for 1 to 8 hours, preferably for 6 hours, and the supernatant is removed by centrifugation. The ultrasonic crushing and centrifugation process is repeated twice, and the obtained precipitate is further ultrasonically crushed and centrifuged to obtain a precipitate; further, the centrifugal speed of the centrifugation is 5000 to 6500 rpm, and the centrifugation time is 10 to 15 minutes.

8. The preparation method according to claim 7, characterized in that: In S2, the ultrasonic crushing process is: ultrasonic crushing the precipitate for 1 to 20 minutes, preferably 10 to 15 minutes, and centrifuging at a centrifugal speed of 11000 rpm for 1 to 10 minutes; taking the precipitate, adding 30 mL of pure water, ultrasonicating again for 1 to 5 minutes, and centrifuging at 11000 rpm for 1 to 10 minutes to obtain a precipitate.

9. A graphite-phase carbon nitride-supported metal single-atom nanozyme prepared by the method described in any one of claims 1 to 8, with graphite-phase carbon nitride as the carrier, and the Cu element content supported per 2g of g-C3N4 substrate is 0.05mmol~1.5mmol, preferably 0.1mmol~0.15mmol.

10. An application of graphite-phase carbon nitride-loaded metal single-atom nanozyme prepared by the method according to any one of claims 1 to 8 in anti-tumor aspects.

Citation Information

Patent Citations

  • Copper ion chelated graphite-phase single-layer C3N4 nano-enzyme and preparation method thereof

    CN112844431A

  • A carbon quantum dot-coated metal single-atom-carbon nitride composite material and its preparation method

    CN112973750B